Internalisation of Ethical Values in Sharia Financial Literacy-Based Curriculum Integration at Islamic Boarding Schools - Istianatud Diniyah; Abdul Jamal (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2026)
This study examines the development of ethical dimensions and Islamic principles in a sharia financial literacy curriculum at the Al-Mujtama Islamic Boarding School in Pamekasan, Madura, East Java. This research employed a qualitative approach within an empirical juridical design. Data were obtained from five informants, including leaders, teachers, and students. Data collection techniques used interviews, observation, and documentation. The study concluded that the integration of sharia financial literacy can be achieved through three main patterns: (1) horizontal curriculum integration, by inserting sharia financial values and principles into existing courses; (2) vertical integration curriculum, through the development of learning materials specifically for sharia financial literacy or management; and (3) co-curricular integration, through extracurricular activities such as sharia investment clubs, business competitions, and industrial internship programs.